INVENTARISASI TUMBUHAN AIR DI DANAU TANJUNG PUTUS DESA BULUH CINA DAN POTENSINYA SEBAGAI MODUL BIOLOGI SMA - Aryani Kodriyana; Nursal '; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Riau Province has the largest aquatic forest area in Sumatra. One of aquatic forest area located in Buluh Cina Village. This village has a natural ecosystem, that is Buluh Cina Lake. The aim of this study is to describe species of aquatic plant in Tanjung Putus Lake as environment potency as the study source for applying environmental base learning. This study held on September untill November 2016. The sample in this study is community of aquatic plant in Tanjung Putus Lake. This descriptive study with purpossive sampling method applying a line transect combined with 1x1 m plotting started from shoreline to the deeper lake area. This study found 26 species of aquatic plant. These aquatic plant consist of two type of aquatic plant, those are submersed plant and root floating plant. While two other type of aquatic plant was not found in this lake. Some of aquatic plant are familiar to the Buluh Cina people.. This 26 species consist of 18 family and 18 ordo. This study result adopted as modul design by analizing Curriculum of 2013.Key words: Aquatic Plant,Inventory, Lake, Modul,